Aksi Bersih Sungai dan Edukasi Lingkungan Berbasis Komunitas sebagai Strategi Pengelolaan Sungai Partisipatif di Kota Batu - Agung Suprianto; Alfi Sahrina; Cinde Ririh Windayu; Luly Triningsih (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
The problem of river pollution in the Batu City tourist area, especially the Brantas River and Kali The problem of river pollution in the tourist areas of Batu City, particularly the Brantas River and Kali Lanang River, raises ecological concerns and negatively impacts tourism quality. Based on observations and interviews with environmental communities and residents living along the riverbanks, it was found that public awareness of maintaining river cleanliness is still low. This community service program aims to increase public environmental awareness and create participatory river management. The main activities include environmental education, training on the use of floating litter trap technology, and river clean-ups carried out collaboratively using the Penta Helix approach. The results have resulted in a 60% increase in environmental literacy, the implementation of river clean-ups by five communities/agencies, and a significant reduction in the volume of waste along the riverbanks. This approach has proven effective in building ecological awareness and can be replicated in other tourist areas.